Simulation techniques in financial risk management - Chan, Ngai Hang; Wong, Hoi Ying 1974- (Hoboken Wiley, 2015)
"More than 300 exercises at the end of each chapter provide the opportunity for readers to apply new concepts and test their knowledge. Answers for selected exercises (at the rear of the book) offer additional insights to help readers consolidate their understanding"-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Finance -- Simulation methods; Risk management -- Simulation methods